Urinary concentrations of phenols in association with biomarkers of oxidative stress in pregnancy: Assessment of effects independent of phthalates. (October 2019) - Ferguson, Kelly K.; Lan, Zhao; Yu, Youfei; Mukherjee, Bhramar; McElrath, Thomas F.; Meeker, John D.
Abstract: Background: Maternal exposure to environmental phenols is common in pregnancy and has been linked to preterm birth, preeclampsia, and reduced fetal growth. One potential mechanism may be through increased maternal oxidative stress. Objective: We examined the associations between a panel of 10 urinary phenols, including dichlorophenols, benzophenone-3, parabens, triclosan and triclocarban, and bisphenol-S, and two urinary oxidative stress biomarkers, 8-hydroxydeoxyguanosine (8-OHdG) and 8-isoprostane. All exposure and outcome biomarkers were measured at 4 time points in pregnancy. Methods: We used repeated measures models to examine the association between repeated exposure and outcome biomarkers. Additionally, we used adaptive elastic net (AENET) to identify non-null associations accounting for the correlation structure of exposures, both for phenols and urinary phthalate metabolites that were previously associated with the oxidative stress biomarkers in our study population. Results: In adjusted repeated measures models, we observed that dichlorophenols, benzophenone-3, triclosan, and some parabens were associated with increases in both oxidative stress biomarkers. The greatest effect estimates were observed for 2, 5-dichlorophenol; an interquartile range (IQR) increase in this compound was associated with a 15.2% (95% confidence interval [CI] = 11.0, 19.6) increase in 8-OHdG and a 16.7% (95% CI = 9.66, 24.2) increase in 8-isoprostane. Bisphenol-S detection was associated with a clear increase in 8-isoprostane (18.5%, 95% CI = 7.68, 30.5) but a more modest increase in 8-OHdG (6.18%, 95% CI = −0.27, 13.1). However, AENET models did not consistently select any of the phenols as predictors of 8-OHdG or 8-isoprostane when phthalate metabolites were included in the model. Conclusion: Overall, urinary phenols were associated with increases in biomarkers of oxidative stress in pregnancy but either to a lesser extent, or due to correlation with, urinary phthalate metabolites. Highlights: We examined the association between urinary phenols and oxidative stress biomarkers. Urinary exposure and outcome biomarkers were measured at 4 study visits in pregnancy. Phenols were associated with modest increases in both oxidative stress biomarkers. AENET selected the drivers of associations from the mixture of phenols and phthalates. Mixture results suggested phthalates were driving phenol-oxidative stress associations.